Upper atmosphere response to extratropical cyclones - Zakharov Victor; Solovieva Maria; Shalimov Sergey; Akperov Mirseid; Korkina Galiya; Bulatova Nadezhda (Solar-Terrestrial Physics)
We have examined the response of the lower and upper ionosphere to the passage of extratropical cyclones in 2014–2023, using measurements made at regional ultra-long-wave radio stations and satellites of the Swarm mission in the Far Eastern region of Russia. For twelve cyclones, we have found that disturbances in the lower ionosphere, observed in VLF signal amplitude and phase variations, as well as their associated electron density variations in the upper ionosphere during the active stage of the cyclones, correspond to the passage of atmospheric internal gravity waves and their dissipation, as evidenced by several examples. We have studied the mechanisms of the influence of internal atmospheric waves on the ionosphere, which make it possible to interpret the VLF signal phase variations observed in the lower ionosphere and the electron density variations in the upper ionosphere.